La fidelidad - Ruiz Malo, Emilio (Mercurio Peruano, 2013)
Faithfulness is defined as the result of the adhesion to a value which is discovered and worthy, because it is radical in the being. Faithfulness, therefore, cannot be something else but to become close to other beings and maintain their presence (promise). It begins by being faithful to one self to arrive at the collaboration of another, who I need to revalue myself. In this sense, faithfulness implies a life exchange, which will demand organizing faithfulness and integrating it in a transcendent order. Finally we state that regret is most of times the only possibility of returning to commitment.